A Comparison of Socially Responsible and Conventional Investors - McLachlan, Jonathan (Journal of business ethics, 2004)
Socially responsible investment is a rapidly emerging phenomenon within the field of personal investment. However, the factors that lead investors to choose socially responsible investment products are not well understood, especially in an Australian context. This study provides a comparative examination of conventional and socially responsible investors, with the aim of identifying such factors. A total of 55 conventional investors and 54 ethical investors participated in the study by completing mailed questionnaires about their investment and general behaviour and their attitudes and beliefs. Results indicated some important differences between socially responsible and conventional investors in their beliefs of the importance of ethical issues, their investment decision-making style, and their perceptions of moral intensity. These results support the notion that socially responsible investors differ in critical ways to conventional investors, and are discussed in terms of theoretical and practical implications.